2018
DOI: 10.1128/jb.00733-17
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Features of the Enterococcal pCF10 Sex Pheromone Response and the Biology of Enterococcus faecalis in Its Natural Habitat

Abstract: Conjugative transfer of plasmids in enterococci is promoted by intercellular communication using peptide pheromones. The regulatory mechanisms that control transfer have been extensively studied However, the complicated systems that regulate the spread of these plasmids did not evolve in the laboratory test tube, and remarkably little is known about this form of signaling in the intestinal tract, the primary niche of these organisms. Because the evolution of strains and their coresident pheromone-inducible pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…through natural or acquired resistance mechanisms (4,5). Recently, several reports have shown that the increased incidence of multidrug-resistant enterococci, including vancomycin (VAN)-resistant and linezolid (LZD)-resistant strains, has limited our treatment choices, and controlling multidrug-resistant E. faecalis infections has become a critical need in clinics (4)(5)(6).…”
mentioning
confidence: 99%
“…through natural or acquired resistance mechanisms (4,5). Recently, several reports have shown that the increased incidence of multidrug-resistant enterococci, including vancomycin (VAN)-resistant and linezolid (LZD)-resistant strains, has limited our treatment choices, and controlling multidrug-resistant E. faecalis infections has become a critical need in clinics (4)(5)(6).…”
mentioning
confidence: 99%
“…Coordinated regulation of conjugal transfer genes is critical, as efficient conjugation systems must identify compatible partners and culminate with the stable maintenance of the transferred mobilized DNA in the resulting transconjugant (4). This coordination is exemplified by some conjugative systems that encode pheromones to regulate donor and recipient functions (5)(6)(7).…”
mentioning
confidence: 99%
“…In all cases, animal models were inoculated with donor and recipient strains each at 10 7 colony-forming units (CFU) and above. Typical enterococcal numbers within humans range between 10 5 and 10 7 CFU per gram; thus, the abovementioned results reflect the transfer of PRP under conditions of dysbiosis [17][18][19][20][21].…”
Section: Significance Of the Prp Systemmentioning
confidence: 88%
“…The 5 0 region is regulatory and is followed by the adherence module, which mediates cell aggregation. The distal end of the operon encodes the plasmid mobilisation genes, consisting of a type 4 secretion system (T4SS) utilised as a bacterial mating channel between donor and recipient cells, in addition to plasmid processing genes [20].…”
Section: Conjugation and Plasmid Transfermentioning
confidence: 99%